Desarrollo de sistema web de control y apoyo Académico para los docentes en la unidad educativa Eugenio espejo del cantón Babahoyo provincia de los Ríos - Gorotiza León, Stalin Santiago (2014)
This project, a Web platform for monitoring the academic progress of teachers in the UEEE ensuring Teaching Standards Learning prepared by the Ministry of Education, this platform will also support for Teachers in the monitoring process was designed and perform compliance activities by students, parents appointments with families, which will be used as evidence in case of problems or academic conflicts, which agilitaría the process easier and faster. The Web platform was performed using the following applications for development of web systems:  PHP Hypertext Pre-processor.  MySql Database The platform will be used by Managers, Teachers and Students of the institution which will be assigned a username and password by respective function within the system. Usurious by role type have assigned the features within the system, within the system will see the following options: teachers  Register your respective academic progress.  Monitor and topics in previous classes.  Change your password.  Supervise compliance with established academic programs for each of the learning units by the Teachers.  Reports Get every academic progress...